THE ROLE OF CULTURAL CONTEXT IN PROVERB TRANSLATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article the author discussed the influence of cultural features while translating a particular text in Uzbek and English languages in which proverbs are used. As we know that proverbs are a concise, brief, clear form of oral wisdom and can represent a particular country and its inhabitants` lifestyle, tradition, culture. This article discussed the relevance and significance of culture in proverb translation as well as the clarified conclusions drawn from the writings of well-known authors and academics. These issues have been discussed:1. How culture influence translation;2. What is the role of text in proverb translation, and 3. What is the main role of translators in proverb translation? This article highly emphasizes the challenges of interpreting cultural nuances while translating proverbs, and reveals the key points to overcome this issue.